Java™ Application Development on Linux® - Albing, Carl; Schwarz, Michael (Pearson, 2004)
Linux is the fastest-growing Java development platform because it saves money and time by serving as a platform for both development and deployment. But developers face significant platform-specific challenges when managing and deploying Java applications in a controlled production environment. Written for Java and Linux developers alike, Java™ Application Development on Linux® is the hands-on guide to the full Java application development lifecycle on Linux. Determined to spare other developers hours of trial and error, Albing and Schwarz demonstrate the platform, tools, and application development by showing realistic, easy-to-follow examples. After a simple command-line application introduces basic tools, this program leads readers through business-logic object analysis, database design, Java servlet UIs, Java Server Pages (JSP) UIs, Swing GUIs, and Standard Widget Toolkit (SWT) GUIs. Scaling up to the enterprise level provides the opportunity to use both the JBoss Application Server and the Apache Geronimo Application Servers, and Enterprise JavaBeans (EJB). Readers learn how to Use development tools available on Linux, such as the GNU Compiler for Java (gcj), Ant, the NetBeans IDE, IBM's Eclipse Java IDE, JUnit, and SunONE Studio Develop business logic layers using Java DataBase Connectivity (JDBC) Add a Web interface using servlets and JSPs Add a GUI using Sun's Abstract Window Toolkit (AWT) and IBM's SWT Deploy EJBs in Linux The authors conclude by demonstrating how a hierarchy of budgets can be created, tracked, and shared with Concurrent Versions System (CVS). A companion Website includes all source code and a link to each tool described. Java™ Application Development on Linux® can propel you from a standing start to the full-speed development and deployment of Java applications on Linux.
Online resource; Title from title page (viewed November 22, 2004)
Keywords: Linux; Application software -- Development; Java (Computer program language); Logiciels d'application; Développement; Java (Langage de programmation); Application software; Development